Study on the relations of ionic conductivity and transport properties of alginate-PVA based bio-polymer blend electrolytes system - S. N. A., Azahar; N. M., Ghazali; Diantoro, M.; Ahmad Salihin, Samsudin (Penerbit Universiti Malaysia Pahang, 2023)
The growing interest in green energy storage materials has led to a renewed focus on creating biopolymer materials as electrolytes for electrochemical devices. In addition to being environmentally benign, it may result in lower costs and many financial prospects. This study sheds light on the protonation process of bio-polymer blend electrolytes based on alginate-poly (vinyl alcohol) (Alg-PVA) synthesized using the solution cast method and doped with varying concentrations of ammonium sulphate (NH4)2SO4. The impedance spectroscopy obtained the Cole-Cole plot, and the bulk resistance value decreased when (NH4)2SO4 was added. The calculated ionic conductivity showed the optimum value at 1.26 × 10-4 S cm-1 for a sample containing 15 wt.% of (NH4)2SO4. The dielectric responses were used to assess the transport parameters of ion conduction, and it was shown that the principal causes of the increase in ionic conductivity are increased ion mobility and diffusion coefficient caused by the addition of (NH4)2SO4.